Prevalence of Skin and Soft Tissue Infections in Diabetic Patients in a District Headquarters Hospital of, Pakistan - Aisha Anwer, Abdul Kamil Ghummon, Muhammad Saqib Munir Rana, Sadia Rasheed, Faran Hamid, Jaweria Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes has become the most prevalent endocrine disorder as it has continued to increase. Diabetes mellitus cases are remarkably increasing in our country every year. Diabetes is characterized by a pathophysiology that leaves diabetic patients more prone to infection and to developing skin and soft tissue infections that are more complicated. The risk of infection is increased in diabetic patients, and their mutation potential is detrimental, resulting in a higher morbidity and mortality rate than in the general population. Infections of the skin and soft tissues (SSTIs) involve microbial invasions, and they differ in presentation and severity. A total 445 participants 15 to > 40 years of age participated in this study. Out of total respondent, 48.53% and 51.46% were male and female, respectively. Among the total, the highest percentage of the respondent were around 36- 40 years old 52 (22.70%) followed by 31-35 years old 44 (19.65%), 26-30 year old (13.27%), > 40 years old (13.10%), 21-25 years old 29 (12.66%), 16-20 years old 23 (12.04%) and 10-15 years old 20 (8.73%). Out of total 216 males, 179 (82.87%) were infected with soft and tissue infection while out of total 229 females, 206 (89.95%) were infected with soft and tissue infection. Overall prevalence of soft and tissue infection in patients of diabetic mellitus was 86.51%. The maximum respondent belonged to rural areas while minimum respondents from urban areas. 37.66% mild level of exercise was recorded in diabetic patients followed by 25.71% moderate level, and 19.74% heavy level of exercise recorded. Only 16.88% of patients recorded no level of exercise. Majority of respondents used oral medications (51.63%) followed by insulin (47.62%), do exercise (15.76%) and use nutritious food or fruits (9.59%). The study concluded that patients with poorly controlled and uncontrolled blood glucose levels were more likely to develop skin and soft tissue infections. In order to achieve favorable postoperative outcomes, it is essential to make fast and case-adapted therapeutic decisions, as well as to observe the patient's general condition and his wound on a daily basis. Keywords: Diabetes